Pharmacotherapeutic adherence in hypertensive patients in the Integral Center of the Older Adult in Santa Anita – Lima - Ventocilla, Norma (2020)
The objective of this work was to determine the degree of pharmacotherapeutic adherence of patients with arterial hypertension in the Integral Center of the older adult (CIAM) of Santa Anita-Lima. It is a descriptive and prospective study. 27 patients from 59 to 88 years old participated. Two tests were used for adherence analysis: that of Morisky-Green-Levine and that of Hermes. To evaluate the concordance of results between both tests, the McNemar test was used. A 30 % adherence was obtained to antihypertensive treatment with the Morisky-Green-Levine test and a 41 % adherence with the Hermes test. When applying the McNemar test, in both tests were found 5 (18.5 %) adherent patients and 13 (48.1 %) nonadherent; with a total concordance of results between the both of them of 66.6 %.